The physical state of lipid nanoparticles influences their effect on in vitro cell viability - Petersen, Silvia; Steiniger, Frank; Fischer, Dagmar; Fahr, Alfred; Bunjes, Heike (European Journal of Pharmaceutics and Biopharmaceutics, 2011)
Although lipid nanoparticles represent potent drug carriers, for many formulations toxicity data are rare. Thus, in this study, the effect of different lipid nanoparticles on the cell viability of L929 mouse fibroblasts was systematically investigated using the MTT assay. The formulations were composed of trimyristin, tristearin or cholesteryl myristate stabilized with poloxamer 188, polysorbate 80, polyvinyl alcohol or a blend of soybean phospholipid and sodium glycocholate. Depending on lipid and storage conditions, the nanoparticles were prepared in different physical states or crystal modifications leading to different particle shapes. The cell viability was influenced considerably by the physical state of the particle matrix with crystalline nanoparticles causing a stronger decrease in viability than the corresponding liquid or liquid crystalline particles. Effects on the cell viability were also related to the type of matrix lipid, stabilizer and the particle shape. However, the effects of differently shaped particles of different polymorphic modifications of crystalline tristearin were comparable. The low viability caused by poloxamer 188-stabilized particles could be correlated with a strong cell uptake which was investigated by confocal laser scanning microscopy. © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cell viability; Cytotoxicity; L929 mouse fibroblasts; Lipid nanoparticles; Particle shape; Physical state